Not One Step Back : History's Great Sieges - Windrow, Martin (London Quercus Pub., 2009)
The dramatic stories of history's gret sieges: Tyre, Jerusalem, Acre, Chateau-Gaillard, Constantinople, Tenochtitlan, Malta, Chittor Garh, Nagashino, Londonderry, Yorktown, Gibraltar, The Alamo, Vicksburg, and more. Includes maps and illustrations, complemented by fascinating asides on tactics, weaponry and life under siege. An enthralling overview of more than 2000 years of military history.
Include Index, Maps and Illustration
Keywords: Military history -- Siege warfare -- Sieges